Unfulfilled promises of diversity: a decolonial assessment of the basic level English education in Nepal - Purna Chandra Bhusal; Raj K. Baral (Cogent Education)
The Constitution of Nepal (2015) designates Nepal as a multilingual country, and the most recent population census of 2021 records that 142 ethnic groups speak 124 languages across the nation. However, most languages in Nepal exist only in oral forms and even the government-prescribed school textbooks are monolingual, at best bilingual. This article explores the extent to which the Basic Level English Education (BLEE) in Nepal makes an epistemic shift to protect and promote multilingual and multiethnic diversity of the nation. To do so, drawing upon the decolonial concept of epistemic shift and delinking or localization, the article employs a method of thematic content analysis of four official documents: the National Education Policy (NEP) (2019), National Curriculum Framework (NCF) (2019), Basic Level curriculum, and the first unit of the Basic Level English (BLE) textbooks. The article concludes that BLLE in Nepal hardly makes a decolonial epistemic shift to promote and protect multilingual and multiethnic local realities, thereby necessitating further research for the revision and reformation of the entire corpus of BLEE in Nepal.